Uso de plasma rico em plaquetas em úlceras de córnea em cães - Merlini, Natalie B. [UNESP]; Fonzar, Joice Furtado [UNESP]; Perches, Cíntia Sesso [UNESP]; Sereno, Maria Guadalupe [UNESP]; Souza, Vivian Lima de [UNESP]; Rodas, Natália Rodrigues [UNESP]; Padovan, Carlos Roberto [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Ranzani, José Joaquim Titton [UNESP] (My University, 2014)
This study aims to clinically and macroscopically evaluate the adjuvant therapy with platelet-rich plasma in the form of eyedrops or clot, for corneal ulcers in dogs treated at the Veterinary Ophthalmology Service. We analyzed 20 eyes diagnosed with ulcerative keratitis, divided into two experimental groups. The eyedrop group (GC) was composed of eyes treated topically with eyedrops of autologous plateletrich plasma (PRP), and the clot group (GT) was composed of eyes treated with a platelet-rich clot and covered with a third eyelid for retention of the clot. The groups were evaluated by clinical and macroscopic analysis and by the analysis of epithelial defect reduction, at different times, at three, five, ten, 15 and 30 days, except for the third day in GT. The coverage of the third eyelid was removed on the fifth day. In both groups the inflammation signs reduced, there was an improvement in ocular sensibility and proper repair of epithelial defect. All GT eyes and 70% GC eyes showed complete healing on the fifth day, the remainder of GC completed healing on the tenth day. PRP in the form of eyedrops and clot is an excellent adjuvant therapy to be instituted in the clinical treatment for corneal ulcer in dogs, because it decreases the inflammatory signs and the ocular pain and it potentially assists in healing epithelial defects.

Este trabalho teve por objetivo avaliar, clínica e macroscopicamente, o tratamento adjuvante com plasma rico em plaquetas na forma de colírio ou tampão, em úlceras de córnea de cães atendidos no Serviço de Oftalmologia Veterinária. Foram analisados 20 olhos com diagnóstico de ceratite ulcerativa, distribuídos em dois grupos experimentais. O grupo colírio (GC) foi constituído por olhos tratados topicamente com colírio autólogo de plasma rico em plaquetas (PRP), e o grupo tampão (GT) por olhos submetidos ao tratamento à base de tampão sólido de PRP, associado ao recobrimento com terceira pálpebra para retenção deste. Os grupos foram avaliados, por meio de avaliação clínica, macroscópica e análise da redução do defeito epitelial, em diferentes momentos, aos três, cinco, dez, 15 e 30 dias, com exceção do terceiro dia no GT. O recobrimento da terceira pálpebra foi removido no quinto dia no GT. Em ambos os grupos, houve redução dos sinais de inflamação, melhora na sensibilidade ocular e adequada reparação do defeito epitelial. Todos os olhos do GT apresentaram completa cicatrização no quinto dia e 70% no GC, atingindo a totalidade no 10º dia. O PRP na forma de colírio ou tampão é uma excelente terapia adjuvante a ser instituída no tratamento clínico da úlcera de córnea em cães, pois atua na diminuição dos sinais inflamatórios, da dor ocular e auxilia potencialmente na cicatrização do defeito epitelial.
Use of platelet rich plasma on corneal ulcers in dogs
Keywords: Dogs; Epithelial defect; Growth factors; PRP; Cão; Defeito epitelial; Fatores de crescimento; PRP